1999
DOI: 10.1007/s002709900334
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Absence of the Internal Carotid Artery

Abstract: We report three cases of congenital absence of an internal carotid artery (ICA), diagnosed incidentally by digital subtraction angiography. The analysis of the cases is based on the classification of segmental ICA agenesis proposed by Lasjaunias and Berenstein. Usually the patients with this rare vascular anomaly are asymptomatic; some may have symptoms related to cerebrovascular insufficiency, compression by enlarged intracranial collateral vessels, or complications associated with cerebral aneurysms. Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 8 publications
1
51
0
Order By: Relevance
“…The anomaly is often detected as an incidental Wnding. However, when symptoms are present they include recurrent headache, blurring vision, hearing loss, hemiparesis with or without cranial nerve palsy, Horner syndrome, and intracranial haemorrhage due to ruptured aneurysms [2]. Absence of the ICA is associated with 25-34% of aneurysm formation on the circle of Willis [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…The anomaly is often detected as an incidental Wnding. However, when symptoms are present they include recurrent headache, blurring vision, hearing loss, hemiparesis with or without cranial nerve palsy, Horner syndrome, and intracranial haemorrhage due to ruptured aneurysms [2]. Absence of the ICA is associated with 25-34% of aneurysm formation on the circle of Willis [2,10].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between right and left ICA agenesis is 1:3. 8 Very few cases of ICA agenesis have been reported in children, because of the collateral supply, which is sufficient to maintain cerebral perfusion. 4 ICA agenesis was discovered in our patient during evaluation for syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that ICA agenesis is more often seen on the left, and the left/right ratio of the pathology is 3:1 (6). ICA agenesis has been suggested to be a developmental variation, although its exact cause is unknown (7). The objective of this study was to report a patient with ICA agenesis who had initially presented with facial burning sensation, was diagnosed with left ICA occlusion, and referred to our center for further investigation and interventional treatment, and to discuss the differential diagnosis of internal carotid artery agenesis and occlusion.…”
Section: Introductionmentioning
confidence: 99%